(untitled) (Bangladesh Journal of Infectious Diseases, 2026)
Background: Chitosan hydrogels are biocompatible, biodegradable, and pH-sensitive. Grafting them with fluorogenic and chromogenic substrates allows rapid in-situ detection of bacterial enzymes via fluorescence and absorbance, offering a faster alternative to traditional methods. Objective: The aim of this study was to develop and evaluate fluorogenic and chromogenic chitosan hydrogels for rapid detection of α-glucosidase and β-galactosidase and assess pH effects on their enzyme responses. Methodology: This study was conducted at the Department of Pharmacy, East West University, Dhaka, Bangladesh (Feb–Dec 2019). Chitosan-based hydrogels were prepared and grafted with fluorogenic (MUD) and chromogenic (X-GAL) substrates to detect α-glucosidase and β-galactosidase. Films were formed on silicon wafers and modified via EDC/NHS coupling. Enzyme reactions, pH effects, and hydrogel stability were evaluated using fluorescence and absorbance measurements. Results: The enzymatic reaction of MUD-grafted NSC with α-glucosidase released 4-methylumbelliferone (4-MU), showing strong fluorescence at 450 nm, which increased with dye concentration and was highly pH-dependent. Kinetic studies revealed that 4-MU production was fastest at pH 6.0 and slowest at pH 8.0, with maximum concentrations of 20.6 µM, 11.2 µM, and 1.68 µM at pH 6.0, 7.0, and 8.0, respectively. X-GAL-modified NSC hydrogels reacted with β-galactosidase to release a visible blue dye, with absorbance peaks at 650 nm. Aging studies showed that sterilized hydrogels exhibited 44% dye loss over 4 weeks, while non-sterilized hydrogels showed only 17.2% loss, indicating better retention of enzymatic activity in non-sterilized samples. Conclusion: Fluorogenic and chromogenic chitosan-based hydrogels effectively detect bacterial enzymes α-glucosidase and β-galactosidase. The enzymatic responses are strongly influenced by pH, and the hydrogels maintain functionality for up to 4 weeks, demonstrating potential for rapid in-situ bacterial detection. Bangladesh Journal of Infectious Diseases, December 2025;12(2):273-284